Levosimendan prevents doxorubicin-induced cardiotoxicity in time- and dose-dependent manner: implications for inotropy. Issue 3 (22nd June 2019) - Efentakis, Panagiotis; Varela, Aimilia; Chavdoula, Evangelia; Sigala, Fragiska; Sanoudou, Despina; Tenta, Roxane; Gioti, Katerina; Kostomitsopoulos, Nikolaos; Papapetropoulos, Andreas; Tasouli, Androniki; Farmakis, Dimitrios; Davos, Costantinos H; et al.
Abstract: Aims: Levosimendan (LEVO) a clinically-used inodilator, exerts multifaceted cardioprotective effects. Case-studies indicate protection against doxorubicin (DXR)-induced cardiotoxicity, but this effect remains obscure. We investigated the effect and mechanism of different regimens of levosimendan on sub-chronic and chronic doxorubicin cardiotoxicity. Methods and results: Based on preliminary in vivo experiments, rats serving as a sub-chronic model of doxorubicin-cardiotoxicity and were divided into: Control (N/S-0.9%), DXR (18 mg/kg-cumulative), DXR+LEVO (LEVO, 24 μg/kg-cumulative), and DXR+LEVO (acute) (LEVO, 24 μg/kg-bolus) for 14 days. Protein kinase-B (Akt), endothelial nitric oxide synthase (eNOS), and protein kinase-A and G (PKA/PKG) pathways emerged as contributors to the cardioprotection, converging onto phospholamban (PLN). To verify the contribution of PLN, phospholamban knockout (PLN −/− ) mice were assigned to PLN −/− /Control (N/S-0.9%), PLN −/− /DXR (18 mg/kg), and PLN −/− /DXR+LEVO (ac) for 14 days. Furthermore, female breast cancer-bearing (BC) mice were divided into: Control (normal saline 0.9%, N/S 0.9%), DXR (18 mg/kg), LEVO, and DXR+LEVO (LEVO, 24 μg/kg-bolus) for 28 days. Echocardiography was performed in all protocols. To elucidate levosimendan's cardioprotective mechanism, primary cardiomyocytes were treated with doxorubicin or/and levosimendan and with N omega-nitro-L-arginine methyl ester (L-NAME), DT-2, and H-89 (eNOS, PKG, and PKA inhibitors, respectively); cardiomyocyte-toxicity was assessed. Single bolus administration of levosimendan abrogated DXR-induced cardiotoxicity and activated Akt/eNOS and cAMP-PKA/cGMP-PKG/PLN pathways but failed to exert cardioprotection in PLN −/− mice. Levosimendan's cardioprotection was also evident in the BC model. Finally, in vitro PKA inhibition abrogated levosimendan-mediated cardioprotection, indicating that its cardioprotection is cAMP-PKA dependent, while levosimendan preponderated over milrinone and dobutamine, by ameliorating calcium overload. Conclusion: Single dose levosimendan prevented doxorubicin cardiotoxicity through a cAMP-PKA-PLN pathway, highlighting the role of inotropy in doxorubicin cardiotoxicity. Graphical Abstract: